A dialogue among indigenous groups: the experience of two encounters mediated by the video - Dominique T. Gallois; Vicent Carelli (Revista de Antropologia, 1995)
The article analyses the role of video in intercultural communication from the interaction that is established among indigenous groups which met each other by vídeo images, afterwards, they ended up meeting personally, "in real life". The description of two of these encouters, between Waiãpi (AP) and Zo'e (PA), and between Gavião/Parkatêjê (PA) and Krahô (TO), provides context to the documentaries produced by the project Vídeo nas Aldeias/CTI about these experiences.